2016
DOI: 10.3389/fphys.2016.00340
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Architectural and Functional Adaptations Following Long vs. Short Muscle Length Eccentric Training

Abstract: Most common preventive eccentric-based exercises, such as Nordic hamstring do not include any hip flexion. So, the elongation stress reached is lower than during the late swing phase of sprinting. The aim of this study was to assess the evolution of hamstring architectural (fascicle length and pennation angle) and functional (concentric and eccentric optimum angles and concentric and eccentric peak torques) parameters following a 3-week eccentric resistance program performed at long (LML) vs. short muscle leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 47 publications
7
71
2
1
Order By: Relevance
“…Thus, the joint positions during the NH curl training may have contributed to the lack of fascicle length change (and the lack of shift in maximal eccentric torque towards longer lengths) seen after the intervention. Additionally, when fascicle increases have been shown to occur, they increase fairly quickly; 3-5 weeks into eccentric training (Blazevich et al 2007;Baroni et al 2013;Guex et al 2016;Bourne et al 2016). The current NH intervention length of 6 weeks was similar to previous studies (Iga et al 2012;Delahunt et al 2016).…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, the joint positions during the NH curl training may have contributed to the lack of fascicle length change (and the lack of shift in maximal eccentric torque towards longer lengths) seen after the intervention. Additionally, when fascicle increases have been shown to occur, they increase fairly quickly; 3-5 weeks into eccentric training (Blazevich et al 2007;Baroni et al 2013;Guex et al 2016;Bourne et al 2016). The current NH intervention length of 6 weeks was similar to previous studies (Iga et al 2012;Delahunt et al 2016).…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archsupporting
confidence: 81%
“…Sharifnezhad et al (2014) confirmed that fascicle length increases are dependent on the range of lengths used during the intervention; showing the vastus lateralis fascicle lengths increased in the leg that exercised at a longer muscle length (25-100° knee flexion), with no change in fascicle length for the leg exercised at a shorter muscle length (25-65° knee flexion) after training. Further, Guex et al (2016) confirmed that hamstring fascicle length increases after a dynamometer-based eccentric strength intervention are dependent on the muscle length during training; BFLH fascicle lengths increased more when trained at a longer muscle length (80° hip flexion), compared to shorter muscle length (0° hip flexion). Thus, the joint positions during the NH curl training may have contributed to the lack of fascicle length change (and the lack of shift in maximal eccentric torque towards longer lengths) seen after the intervention.…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archmentioning
confidence: 54%
“…This hypothesis seems supported by other studies (McMahon et al, 2014; Guex et al, 2016), which found a greater increase in fascicle length of VL when training at greater ROM of the knee joint. Nonetheless, Noorkõiv et al (2014) showed that isometric training at longer muscle lengths (i.e., thus almost re-producing an ECC contraction scenario) can induce a substantial increase in Lf.…”
Section: The Contribution Of Chronic Concentric Vs Eccentric Loadingsupporting
confidence: 74%
“…All three studies found that isometric training at long muscle lengths (LMLs) was superior to equal volumes of training at short muscle lengths (SMLs) for increasing muscle size . These findings are not surprising as a large portion of the existing literature has demonstrated that dynamic training through a large range of motion is beneficial when hypertrophy is desired . Additionally, contractions at LML tend to produce higher quantities of muscle damage, likely by altering the joint moment arm and increasing mechanical tension when compared to a SML .…”
Section: Discussionmentioning
confidence: 92%